1987
DOI: 10.1002/arch.940060402
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular proteins: The neglected component

Abstract: This paper emphasizes the importance of the protein component of cuticles.Correlation of electrophoretic charge distribution of individual cuticular proteins and physical properties of the cuticles from which they were extracted, as well as interpopulation and interspecies conservation of electrophoretic patterns, are used to argue that individual proteins play precise roles in the cuticle. Glycosylation of cuticular proteins is described, but no function for these modifications is yet known. Analogy is drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 40 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…Chitin and cuticular proteins are the major components of insect cuticle [21,22]. It is noteworthy to mention that the gene coding for chitin synthase, a critical enzyme for chitin synthesis [23-25], had peak expressions at the same stages in which the majority of cuticular protein genes were also highly expressed, indicating that the processes of cuticle formation were activated concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…Chitin and cuticular proteins are the major components of insect cuticle [21,22]. It is noteworthy to mention that the gene coding for chitin synthase, a critical enzyme for chitin synthesis [23-25], had peak expressions at the same stages in which the majority of cuticular protein genes were also highly expressed, indicating that the processes of cuticle formation were activated concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…Also, preliminary data from size fractionations of enzyme-digested cuticular peptides suggested that the inducer(s) is larger than 200 Da. Recent evidence from Candida albicans indicates that induction of an extracellular aspartyl protease is effected by peptides of more than eight residues even though its permeases do not efficiently transport peptides > 6-7 residues (Lerner & Goldman, 1993 (Rebers & Riddiford, 1988) and Hyalophora cercopia (Willis, 1987)] and two species of' Diptera [ Drosophila melanogaster (Snyder e t al., 1982) and Sarcophaga bullata (Henzel e t al., 1985)l. While there is some sequence homology between these proteins and the one protein sequenced from adult locust endocuticle (Talbo e t al., 1991) they differ markedly from the locust exocuticle proteins described above.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the sequences of these proteins are characterized by three types of region: (i) regions enriched in glycine, leucine or tyrosine, (ii) hydrophobic regions wich repeats of an Ala-Ala-Pro-Ala/Val motif often preceded by tyrosine, and (iii) hydrophilic regions, dominated by amino acids with relatively large side chains. Only one adult locust endocuticular protein has been sequenced (Talbo et a/., 1991); it has sequence similarity with a number of proteins from soft larval cuticles from Lepidoptera (Rebers & Riddiford, 1988;Willis, 1987) and Diptera (Snyder e t al., 1982 ; Henzel e t a/., 1985) but is very different from adult locust exocuticle proteins. In particular there are no repeat motifs of Ala-Ala-Pro-Ala/Val.…”
Section: Potential Peptide Inducers From Insect Cuticlementioning
confidence: 99%
“…Infection by these fungi is facilitated by the secretion of extracellular proteases (Charnley and St. Leger 1991; Bidochka and Khachatourians 1990; Bidochka et al 1993; St. Leger et al 1988; Willis 1987). Proteolytic enzymes appear early, in large quantities, during infection, assisting in initial host penetration and in later processes (El-Sayed et al 1993b).…”
Section: Introductionmentioning
confidence: 97%